2012
DOI: 10.1007/s11033-012-2229-0
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic dipeptide cyclo (His-Pro) significantly altered plasma proteome in streptozocin-induced diabetic rats and genetically-diabetic (ob/ob) mice

Abstract: The proteins in plasma perform many important functions in the body, and the protein profiles of the plasma vary under different physiological and pathological conditions. In an attempt to identify novel marker proteins for diabetes prognosis, we examined the effect of hypoglycemic dipeptide cyclo (His-Pro) (CHP) on the differential regulation of plasma proteins in streptozocin-induced diabetic rats and genetically-diabetic (ob/ob) mice. The orally-administrated CHP produced an excellent hypoglycemic effect in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…This may have a relevant impact in disease presentation: alteration of AbPP activity may modulate the amyloidogenic process caused by TTR mutations. As for APOA1, the TTR-FGA interaction seems to be due by dietary alterations: animal experiments with MALDI/TOF mass spectrometry indicated that diabetic rats showed altered proteomic profile, in which FGA and TTR are also included [53]. Our bioinformatic analysis and the data available in literature suggest that these proteins may be involved in the pathogenesis of TTR-related amyloidosis, along with the pathways indicated.…”
Section: Discussionmentioning
confidence: 55%
“…This may have a relevant impact in disease presentation: alteration of AbPP activity may modulate the amyloidogenic process caused by TTR mutations. As for APOA1, the TTR-FGA interaction seems to be due by dietary alterations: animal experiments with MALDI/TOF mass spectrometry indicated that diabetic rats showed altered proteomic profile, in which FGA and TTR are also included [53]. Our bioinformatic analysis and the data available in literature suggest that these proteins may be involved in the pathogenesis of TTR-related amyloidosis, along with the pathways indicated.…”
Section: Discussionmentioning
confidence: 55%
“…A more recent study of HIV-1 proviral gene expression in murine podocytes confirmed mechanisms of glomerulopathy and further showed that concurrent HIV and diabetes were associated with increased acetylation which enhanced expression of senescence and inflammatory markers [39]. A proteomics study also showed elevated plasma levels of a1m in genetically-diabetic mice compared to control mice, and an increasing number of studies have demonstrated the role of proximal tubule injury in both murine and human diabetic renal cells [40,41].…”
Section: Discussionmentioning
confidence: 85%
“…In general its side effects are irritation of stomach other than megadose of more than 1 g of zinc element which could induce serious pathological condition and fatal if taken more than 10 g at a time. CHP side effects are not well established without any report of side effects but some studies of anti-toxicity of CHP have been published [100,117,118]. The long term side effect in humans will be established in our long term clinical trial and in the toxicological studies in dogs with high dose of Cyclo-Z for one year.…”
Section: Mechanism Of Improving Body Weight Controlmentioning
confidence: 98%
“…Cyclo-Z enhances IDE synthesis and stimulates insulin degradation ( Figure 13). In addition, CHP enhances gene expression of factors that ameliorate diabetes and antagonizes factors that induce diabetes [100]. Although CHP or zinc alone is somewhat effective in the control of blood glucose metabolism, Cyclo-Z may be the most effective agent in ameliorating insulin resistance in diabetes and obesity since it stimulates IDE synthesis and enhances beneficial gene expression for diabetes improvement.…”
Section: Mechanisms Of Improving Insulin Sensitivity By Cyclo-z Treatmentioning
confidence: 99%